Dimensi Kecerdasan Emosional Siswa dalam Pembelajaran Pendidikan Agama Islam: Tinjauan Teori Goleman dan Salovey - Ridwan Hermawan; Yurna Yurna; Salsabila Salsabila; Vera Siti Maghfiroh (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The phenomenon of poor emotional management among students, such as irritability, low empathy, and lack of cooperation skills, poses a challenge in Islamic Religious Education (PAI) learning. This study aims to examine the dimensions of students’ emotional intelligence in the context of PAI learning based on the theories of Daniel Goleman and Salovey-Mayer. Using a literature review approach and qualitative content analysis, this research explores various theories, empirical research findings, and expert opinions derived from relevant journals, books, and scholarly works. The results indicate that emotional intelligence plays a crucial role in the success of PAI learning, particularly in shaping students’ character, Islamic morals, and social skills. Goleman’s theory, which emphasizes five main dimensions self-awareness, self-regulation, motivation, empathy, and social skills can be integrated with the Salovey-Mayer model, which outlines the abilities of perceiving, understanding, and managing emotions cognitively. These dimensions can be synergistically implemented in the PAI learning process to achieve holistic Islamic education goals. In this context, PAI learning is not only oriented toward the transfer of religious knowledge but also toward the formation of an Islamic personality through the integration of emotional management with Islamic values. Teachers, as uswah hasanah (exemplary role models), play a vital role in demonstrating emotional management aligned with Islamic teachings, guiding students through the habituation of Islamic behavior, and providing direction that encourages discipline in worship. A comprehensive understanding of Islam, combined with emotional management skills, shapes students who are not only intellectually intelligent but also emotionally and spiritually mature.